New Humanism, General Studies and Pedagogy of Resistance. - Córdoba, María Elena (2021)
In this article we present a set of ideas that flow into one and the same essential proposal, which we formulate in the pages that follow: That it is possible and indispensable to promote a Pedagogy of resistance in order to facilitate and motivate students to develop the inner capacity for Critical Thought, without resorting to indoctrination, persuasion, or any form of behaviorism, even if disguised under the cloak of pseudo-open mindedness. But to achieve such goal, one has to place students at the very center of the process of teaching and learning. Searching for insights that shed light in this endeavor, we have examined a great deal of heterogenous works within the field of Critical Pedagogy. This way we have searched to synthesize in one proposal the latter, with the educational notions from Freire, and the self-emancipatory perspective of New Humanism. The authors of this essay have been educators for many years and in very different cultural and educational contexts, and this work reflects concerns which are not born from theory but from prolonged work in the classroom itself with students very diverse national idiosyncrasies and from different socio-economic backgrounds. Abstract concepts have only given a more elaborate and precise form to a rich empirical experience and to thoughts and intuitions accumulated for a long time. Therefore, this is the main conclusion we want to advance: that no matter how sophisticated, intelligent, creative and well-conceived your theories may be, they are useless if they are not applied in such a way that they are in accordance with the conceptual premises we may sustain.